2021
DOI: 10.1016/j.heliyon.2021.e07943
|View full text |Cite
|
Sign up to set email alerts
|

Geospatial Analysis of Wetland Dynamics on Lake Abaya-Chamo, The Main Rift Valley of Ethiopia

Abstract: plus using interview. Supervised classifications (via ERDAS14 and ArcGIS10.5) were applied to detect land use/ land cover classes. Change matrix model and Kappa coefficients were used for analysis of the land use/land cover dynamics in the lake-wetland. It was found that forest; water body, shrub land, agricultural land, settlement and swamp area were the main land use/land cover classes. Wetland/swamp area has continuously declined throughout 1990-2000, 2000-2010 and 2010-2019 where its magnitude of shrinkag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 31 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…The vegetation cover management in this region is also optimal, and therefore, soil loss and land degradation are low in these zones. Agroforestry activities, already in practice in the study area, need to be intensified and expanded to reduce soil loss (Zekarias et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The vegetation cover management in this region is also optimal, and therefore, soil loss and land degradation are low in these zones. Agroforestry activities, already in practice in the study area, need to be intensified and expanded to reduce soil loss (Zekarias et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…[ 25 ] reported that data generated through in-situ measurements and laboratory analyses of physico-chemical parameters and the plankton communities, when compared with results from the literature, turbidity, salinity, nitrates and soluble reactive phosphorous showed an increasing trend in Lake Abaya. Quantification of the magnitude and rate of LULC dynamics of Lake Abaya-Chamo wetland within 1990–2019 showed that wetland area has continuously declined throughout 1990–2000, 2000–2010 and 2010–2019 where its magnitude of shrinkage in the respective periods was 11.4% (700ha), 16% (867 ha) and 31.3% (1,424 ha) [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…High population densities within the catchments of the Ethiopian Rift Valley Lakes and in the highlands have been associated with a series of deleterious trends, in particular those arising from the clearance of vegetation for agriculture and overgrazing. Quantification of the magnitude and rate of LULC dynamics of Lake Abaya-Chamo wetland within 1990–2019 showed that wetland area has continuously declined throughout 1990–2000, 2000–2010 and 2010–2019 where its magnitude of shrinkage in the respective periods was 11.4% (700ha), 16% (867 ha) and 31.3% (1,424 ha) [ 20 ]. Some of the key challenges to the wetlands of lake Abaya are intensive use of land in the buffer zones for crop production, land loss due to deforestation in the watershed, and eutrophication by nutrients from agricultural fields [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…These unceasing expansion and trends will also be expected by 2035 and 2050 at the expense of forest, shrub and grasslands loss (Table S2). Moreover, the expansion of waterbodies (Figure 4), particularly along the shore side of Lake Abaya might be attributed to the displacement and lateral expansion of the lake's water due to the increase in sediment load, resulting from soil erosion [65][66][67]. Rapid population growth, social instability, land policy, unproductive land and climate change were identified as the key driving forces of LULC changes in the area [33,68].…”
Section: Land Use Land Cover Dynamicsmentioning
confidence: 99%